Risk Management in Production using Quality Risk Approach and FMEA: Manajemen Risiko dalam Produksi menggunakan Pendekatan Risiko Kualitas dan FMEA - Solikha, Nanda Rochimatus; Marodiyah, Inggit (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract: The production process of 600ml AQUA at PT Tirta Investama (AQUA) Pandaan faces significant risks, including non-compliance with standards in bottle density, incorrect packaging labels, unreadable bottle codes, box failures, and barcode rework. These issues pose challenges in maintaining product quality and operational efficiency. Specific Background: With 247 bottles failing density standards and 18 packaging errors occurring daily, effective risk management is crucial. Knowledge Gap: Previous studies have not integrated Quality Risk Management (QRM) and Failure Mode Effect and Criticality Analysis (FMECA) to address production risks in the context of AQUA's operations. Aims: This study aims to identify the highest critical risk points and propose mitigation strategies. Results: Utilizing QRM and FMECA, 42 risks were identified, categorized into 20 acceptable, 21 tolerable, and 1 unacceptable risk, specifically related to pallets stuck on conveyors due to substandard quality. Novelty: The application of these integrated methodologies provides a systematic approach to identifying and mitigating risks in the production process, highlighting the necessity for in-depth inspections by logistics and machine operators. Implications: The findings underscore the importance of rigorous quality control and proactive risk management in manufacturing to enhance product quality and minimize operational disruptions, thus ensuring customer satisfaction and competitiveness in the market. Highlights: Effective risk management is crucial to ensure product quality and operational efficiency. Integration of QRM and FMECA identifies critical risk points in the production process. Regular inspections and quality control can significantly reduce unacceptable risks. Keywords: Risk Management, Production Process, QRM, FMECA, AQUA